Prevalence of Clinical Significant Lesions in Atypical Glandular Cell of Undetermined Significance (AGUS) From Cervical Pap Smear - Methasinee Pothisuwan; Thaovalai Thavaramara; Sumonmal Manusirivithaya; Chadakarn Phaloprakarn; Siriwan Tangjitgamol (The Royal Thai College of Obstetricians and Gynaecologists, 2009)
Objective: To determine the prevalence of clinical significant lesions from the underlying pathology of women with atypical glandular cell of undetermined significance (AGUS) from cervical Pap smear. Materials and Methods: Women with cytologic diagnosis of AGUS from cervicovaginal Pap smears in our institution from January 2000 to June 2008 were identified. Clinical data and their subsequent tissue histologic diagnoses were reviewed. Results: The prevalence of AGUS in 100,648 Pap smears was 0.26% (266 smears); 151 of them had further investigations and were included in the study. The histology/histopathology turned out to be normal and cervicitis in 35 cases (23.2%) and 28 cases (18.6%), respectively, cervical intraepithelial neoplasia (CIN) I in 51 cases (33.9%), CIN II in 18 cases (11.9%), CIN III in 4 cases (2.7%) adenocarcinoma in situ (AIS) in 4 cases (2.7%), invasive adenocarcinoma of cervix in 4 cases( 2.7%), complex hyperplasia with atypia in 2 cases (1.3%) and endometrial adenocarcinoma in 5 cases (3.3%). Conclusions: The clinical significant lesions were found in 37 cases (24.5%) of AGUS cervical cytology, with 6% prevalence of invasive cancers.